Estimation of metal and metalloid in crude oil of newly developed oil field after acid digestion/extraction methods using different devices - Anjum Lashari; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Mohammad Balal Arain; Ayaz Ali Lashari (Journal of Trace Elements and Minerals, 2023)
Background: The contamination of the environment by metals and metalloids occurs due to oil exploration, owing to combustion via automobiles or different industrial activities. Methods: The crude oil obtained from two newly developed oil fields in Tando Allahyar, Pakistan, were analyzed for the physical characteristics of crude oil. Moreover, arsenic (As) and cadmium (Cd) concentrations in crude oil were measured by three digestion/extraction methods, conventional acid digestion (CAD), microwave-assisted acid digestion (MAD), and ultrasonic-assisted extraction (UAE). The inductively coupled plasma emission spectrometry was applied to determined the As and Cd in digests and extracts of crude oil samples. The standard addition method was applied to evaluate the accuracy of all three methodologies at two concentration levels of As and Cd in a composite crude oil sample. Results: Under the optimum operating conditions, the limits of detection obtained from the standard addition curves were lower in the MAD method, whereas higher value was observed for the CAD method. The LOD for As obtained after MAD, CAD, and UAE were observed as (0.072, 0.083, and 0.078) and Cd (0.062, 0.087, and 0.092) µg L−1, respectively. The respective recoveries of As and Cd obtained with MAD were optimum as compared to those obtained by CAD and UAE. However, the recovery of As was lower from the conventional heating system as compared to UAE. Conclusion: The UAE method was easy, efficient, and environmental friendly. The results obtained are comparable with conventional acid heating systems and about 1% lower than those values obtained by MAD. However, the difference in% recoveries between the three digestion/extraction methods of both elements was insignificant (p>0.05).